Effect of Rams, Incubation Time and Dilution Rate on The Motility and Longevity Characteristics of Merino Rams Spermatozoa - Ismaya (Ismaya) (Faculty of Animal Science, Universitas Gadjah Mada, 2006)
File lengkap ada dalam bentuk PDF dibawah ini